Preventing or promoting muscle injuries? Strength training as a risk factor in professional football - Balagué, N.; Hristovski, R.; Pol, R.; Borrallo, A.; García-Retortillo, S. (Apunts Sports Medicine, 2024)
The rate of muscle injuries in professional football has not decreased despite the implementation of preventive strategies. This is commonly attributed to the rise in the number of competitions per season and the rigorous demands of modern football. However, these factors seem insufficient to explain the absence of impact from preventive strategies. Adopting a Network Physiology perspective, we hypothesize that some strength programs focused on reinforcing the most susceptible musculoskeletal structures and increase the muscle mass might contribute to, rather than mitigate, injuries in some players. The aim of this work is twofold: a) explaining why some currently applied strength training methods may promote sports injuries in some players, and b) suggest the use of intermuscular connectivity measures to test the risk of injury. The stability of multilevel neuromuscular synergies operating at various timescales is a crucial factor for adapting to strength training workloads. This stability necessitates long-term adaptation and cannot be assured through rapid strength gains. When neuromuscular synergies become unstable, the vulnerability to injuries rises. Since performance tests offer limited insights into the stability of neuromuscular synergies, we suggest employing recently developed intermuscular connectivity measures for monitoring and tracking players' progress.